2022
DOI: 10.1038/s41598-022-16515-6
|View full text |Cite
|
Sign up to set email alerts
|

Current use of D-dimer for the exclusion of venous thrombosis in hospitalized patients

Abstract: D-dimer assay’s utility for excluding venous thromboembolism (VTE) in hospitalized patients is debatable. We aimed to assess the current use of D-dimer as a diagnostic tool for excluding VTE in hospitalized patients and examine a mandatory age-adjusted D-dimer (AADD) threshold for diagnostic imaging. Retrospective cohort study between 2014 to 2019 that included patients from medical and surgical wards with a positive AADD result drawn during their hospitalization. The outcomes were determining a D-dimer thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The D-dimer test is reliable for ruling out VTE in outpatient and emergency settings, 14,15 and also works well for hospitalized patients. 16 Notably, individuals with psychosis have a higher risk of VTE, [17][18][19] highlighting the importance of regularly checking their D-dimer levels for asymptomatic VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The D-dimer test is reliable for ruling out VTE in outpatient and emergency settings, 14,15 and also works well for hospitalized patients. 16 Notably, individuals with psychosis have a higher risk of VTE, [17][18][19] highlighting the importance of regularly checking their D-dimer levels for asymptomatic VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high negative predictive value for D-dimer in excluding VTE, 72 it is plausible that F3 SNPs associated with elevated D-dimer may also be associated with clinical VTE. However, a meta-analysis of eight studies of venous thrombosis showed no association between rs12029080 and VTE in patients of European ancestry.…”
Section: Clinical Thrombotic Diseasementioning
confidence: 99%
“…There are no well-established intervals for the D-dimers concentration in blood thus their concentration is often subjective above the values of 0.5 µg/ml [76,79]. A disadvantage is that D-dimer has a high sensibility but a low specificity thus a low prediction capacity with many false-positive cases [80,82,83]. Factors like age, pregnancy, inflammatory diseases, cardiovascular diseases and disseminated intravascular coagulation can make the result even more inconclusive.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Factors like age, pregnancy, inflammatory diseases, cardiovascular diseases and disseminated intravascular coagulation can make the result even more inconclusive. The measurement of D-dimer necessitates their association with other biomarkers in order to confirm a diagnostic [81][82][83].…”
Section: Molecular Biomarkersmentioning
confidence: 99%